Tax Policies as a Mechanism to Combat Tax Evasion through Tax Digitalization as a Mediating Variable – A Case Study of the Tax Directorate in Tébessa Province, Using Structural Equation Modeling (SEM-PLS) - bouthaina, Ghrieb; Chibane, samir (Journal of Research in Finance and Accounting, 2024)
This study aimed to explore the impact of tax policies on tax evasion in Tébessa Province, considering tax digitalization as a mediating variable to enhance understanding of the relationship between applied policies and tax evasion behavior. The study applied the Partial Least Squares Structural Equation Modeling (SEM-PLS) methodology to analyze data collected from a sample of 176 employees at the Tébessa Tax Directorate, using a questionnaire as the primary tool for data collection. The results indicated that tax policies alone do not have à direct impact on tax evasion. However, when these policies are enhanced with digitalization, a positive effect in reducing tax evasion is observed. The study confirms that tax digitalization acts as a complete mediator in this relationship, thereby enhancing the efficiency of tax policies in combating tax evasion and increasing compliance. The study recommends the development of electronic tax systems and the updating of policies to align with digital transformation in order to promote tax compliance.